(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
What drives students to engage in dialogues, contribute to discussion, and make enquiries in the classroom? Is the students self-efficacy linked to their actual participation in class? The relationship between students self-efficacy and classroom participation has received relatively little attention and has not been fully explored. Due to the scant literature, this study looks at self-efficacy as theorized by Banduras Social Cognitive theory, in relation to students participation in classroom activities. It seeks to determine whether Banduras theory of self-efficacy has a causal relationship with students frequency and length of participation. Eighty four students were involved in the study. All the participants completed the Classroom Participation Self-Efficacy Scale (CPSES) to determine their self-efficacy level. The video-recording sessions provided the data on the frequency and time spent on classroom participation. The quantitative data were analysed using SPSS Statistics 17.0 software, where descriptive statistics and linear regression analyses were carried out. The results showed that there was a significant relationship between students classroom participation self-efficacy and length of participation. There was also a significant relationship between students classroom participation self-efficacy and frequency of participation. Recommendations are offered to enhance students self-efficacy and promote students classroom participation in context of higher learning.